Design, synthesis and biological activity evaluation of novel 4-((1-cyclopropyl-3-(tetrahydro-2H-pyran-4-yl)-1H-pyrazol-4-yl) oxy) pyridine-2-yl) amino derivatives as potent transforming growth factor-β (TGF-β) type I receptor inhibitors. Issue 16 (15th August 2020) - Tan, Bin; Zhang, Xiaomeng; Quan, Xu; Zheng, Guochuang; Li, Xue; Zhao, Liwen; Li, Wei; Li, Bo
Graphical abstract: Abstract: TGF-β type I receptor (also known as activin-like kinase 5 or ALK5) plays a critical role in the progression of fibrotic diseases and tumor invasiveness and metastasis, as well. The development of small inhibitors targeting ALK5 has been validated as a potential therapeutic strategy for fibrotic diseases and cancer. Here, we developed various 4-((1-cyclopropyl-3-(tetrahydro-2 H -pyran-4-yl)-1 H -pyrazol-4-yl) oxy) pyridine-2-yl) amino derivatives as ALK5 inhibitors. The optimization led to identification of potent and selective ALK5 inhibitors 12r . The compound 12r exhibited strong inhibitory activity both in vitro and in vivo, and pharmacokinetics study showed an oral bioavailability of 57.6%. Thus, compound 12r may provide as new therapeutic option as ALK5 TGF-βR1 inhibitor.